ANALYSIS OF THE EFFECTS OF INFLATION, INTEREST RATES, AND THE EXCHANGE RATE OF THE DOLLAR ON THE RETURN OF COMPOSITE STOCK PRICE INDEX IN INDONESIA STOCK EXCHANGE - Mayasari, Ita; Saraswati, Dwi (Proceeding International Conference of Science Technology and Social Humanities, 2022)
This study analyzes the influence of inflation, interest rates, and exchange rates on the return of the Composite Stock Price Index (CSPI) in the Indonesia Stock Exchange (ISE). The study utilizes a quantitative research method and secondary data from reports on inflation, interest rates, and the dollar exchange rate from the period of 2015-2018, obtained from the website www.bi.go.id. The data is analyzed using unit root tests, multiple linear regression, and hypothesis testing. The results indicate that the variables of inflation, interest rates, and exchange rates are not stationary at the level. The regression analysis shows that inflation has a negative influence on the CSPI, interest rates have a negative influence on the CSPI, and exchange rates have a positive influence on the CSPI. The classical assumption tests reveal no issues of multicollinearity and heteroscedasticity, but there is a problem of autocorrelation. These findings support previous research that demonstrates the influence of inflation, interest rates, and exchange rates on the CSPI. The study also supports previous research that shows a negative impact of exchange rates on the property sector stock prices. This can be explained by the appreciation of the rupiah against the dollar, which affects the marketing of Indonesian products abroad, particularly in terms of price competition. The study concludes that inflation has a negative and insignificant influence on stock prices, interest rates have a negative and insignificant influence on stock prices, and exchange rates have a positive and significant influence on economic growth. Future research is recommended to include other independent variables such as money supply or trade balance to further analyze the impact on the stock market.